A systematic review of the impact of emergency medical service practitioner experience and exposure to out of hospital cardiac arrest on patient outcomes. (October 2020) - Bray, Janet; Nehme, Ziad; Nguyen, Andrew; Lockey, Andrew; Finn, Judith; ,
Abstract: Aim: To conduct a systematic review to evaluate the impact of emergency medical service (EMS) practitioner's years of career experience and exposure to out-of-hospital cardiac arrest (OHCA) on patient outcomes. Methods: We searched electronic databases (Ovid MEDLINE, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, Web of Science Core Collection) from inception until 10 April 2020. Studies were included that examined the exposures of interest on OHCA patient outcomes: good neurological outcome at discharge/30 days, survival to hospital discharge/30 days, survival to hospital and return of spontaneous circulation (ROSC). Prospero Registration: CRD42019153599. Results: We included 7 of 22 observational studies shortlisted. Four of these studies examined the years of career experience of EMS practitioners, and four studies examined their exposure to attempted resuscitation. The evidence for both exposures of interest was assessed as very-low certainty. Overall, we found no association between patient outcomes and years of career experience. However, the best evidence found, from two large studies, suggests greater recent exposure to cases of attempted resuscitation is associated with better outcomes (ROSC/survival to hospital discharge). One of these studies also reports lower survival to hospital discharge when the team attempting resuscitation had no exposure in the previous six-months. Conclusion: Very low certainty evidence suggests higher exposure to attempted resuscitation cases, but not years of clinical EMS experience, is associated with improved OHCA patient outcomes. This review highlights the need for EMS to monitor OHCA exposure, and the need for further research exploring the relationship between EMS exposure and patient outcomes.